Perbandingan Produktivitas Ayam Ras Petelur terhadap Sistem Kandang Terbuka dan Sistem Kandang Tertutup - Ikram Adiputra Jufri; Aisyah Aisyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The cage has an important role in successful production because a comfortable cage will produce maximum productivity. The aim of this research is to determine the comparison of the productivity of laying hens in the Open House system and the Closed House system at Adam Farm. The method used in this research was to collect data by observing recording data obtained from the two cage systems at Adam Farm. The method used is a descriptive method, then a t test is carried out from December 2023 to February 2024 at Adam Farm Magetan, East Java. The results obtained in this research are the average value of feed intake for maintenance with an open system of 119.98 gr/head, while for maintenance with a closed system it is 131.10 gr/head, the average value -The average feed conversion ratio for maintenance with an open system is 2.92 kg, while for maintenance with a closed system it is 2.37 kg, the average value of hen day production for maintenance with an open system. Amounted to 67.68% while with closed system maintenance it was 84.12%, and the average mortality value for maintenance with an open system was 5 animals while with maintenance with a closed system amounting to 9 heads. The conclusion from this research is that maintenance with a closed system produces better productivity than an open maintenance.